The actuality of Paulo Freire's Liberating Pedagogy: paths for Professional and Technological Education? (Research, Society and Development, 2022)
This article aims to analyze how Paulo Freire's liberating pedagogy can contribute to the construction of a proposal for the formation of the working class that strengthens its autonomy and liberation in the current situation in Brazil. This is bibliographic research, with a qualitative approach, carried out through a narrative literature review, whose data were analyzed and interpreted using the content analysis methodology. In order to reach the objective, it was reflected on the Professional Education offered to the Brazilian working class and on the principles and practices of Paulo Freire's pedagogy that can strengthen the training of workers for their empowerment in the world of work. With the theoretical contribution in the Freirean and Professional Education fields of study, it was possible to identify that at present Professional Education in Brazil is still linked to technicism, focusing only on training for the job market. Thus, it was concluded that Paulo Freire's liberating pedagogy, due to its dialogical and problematizing character, remains current because it promotes humanization and the awakening of the subject's critical consciousness, presenting itself as a counterpoint to Technical Professional and Technological Education.